THE DESCRIPTION OF SELF CONTROL IN PERPETRATORS OF CYBERBULYING - Yara Andita Anastasya; Rini Julistia; Widi Astuti (State Islamic University (UIN) Ar-Raniry, 2023)
The use of technology and information can increase the risk of the phenomenon of cyberbullying. One of the factors of cyberbullying is self-control. Individuals with high self-control will be able to instruct and control themselves in facing unexpected situations. In contrast, individuals with low self-control lack instruction and control for themselves; hence they tend to behave negatively. This study engaged a descriptive quantitative method using a cluster random sampling of 100 students. The instrument used in this study was a self-control scale. The data were analyzed by engaging descriptive analysis. The result shows that perpetrators of cyberbullying have moderate self-control. High self-control indicates that students can control their behavior, cognition, and decision. Thus, they can control their behavior in various situations to obtain positive consequences. Low self-control indicates that students do some unacceptable actions to their environment, especially in school. The higher self-control is, the lower the negative behavior individuals will take. Suboptimal self-control is caused by low aspects of self-control in behavior, cognition, and decision. The lowest aspect is behavior control, which means that perpetrators of cyberbullying tend to spend time with their peers. Therefore, self-control does not work optimally.